Determinants of The Fear of The Pandemic and Its Effect on Voting Behavior Among Young Adult Filipinos in The Next Presidential Election - Jose Mari Gabriel R. Tumanan; Archibald Noel M. Po; Kurt Travis G. Arbolante; Miranda Monserrat Y. Bardos (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
With COVID-19 severely impacting several aspects of society, the upcoming 2022 Philippine Presidential Elections will be the first to take place under such unique circumstances. This study provides information on how various determinants of fear of COVID-19 affect the voting behavior of young adult Filipinos. This study utilized a survey consisting of five sections composed of sociodemographic questionnaire, Multidimensional Scale of Perceived Social Support, Core Dimensions of Spirituality Questionnaire, Fear of COVID-19 Scale and a question about political participation. The results showed that individuals with a higher level of social support and higher level of spirituality were more likely to conform to the political ideals of their respective environments (i.e. family & religious institutions) and were more likely to participate in the elections, along with individuals with higher levels of fear